Efficacy of a Synthetic Pentasaccharide, a Pure Factor Xa Inhibitor, as an Antithrombotic Agent – A Pilot Study in the Setting of Coronary Angioplasty - Vuillemenot, Alain; Schiele, François; Meneveau, Nicolas; Claudel, Sophie; Donat, François; Fontecave, Sylvie; Cariou, Roger; Samama, Meyer Michel; Bassand, Jean-Pierre (Thrombosis and Haemostasis, 1999)
Aim of the study. To assess the antithrombotic properties of SR90107/ORG31540, a sulfated pentasaccharide, which enhances specifically antithrombin III mediated inactivation of factor-Xa, in a clinical setting known to promote arterial thrombosis, i.e. coronary angioplasty.Methods and results. Percutaneous transluminal coronary angioplasty (PTCA) was carried out with conventional balloons with a single 5 min intravenous infusion of 12 mg pentasaccharide, and 500 mg intravenous aspirin. Heparin was not allowed before, during PTCA, and within 24 h after PTCA. The primary end point was the rate of abrupt vessel closure during and within 24 h after the procedure. The sample size was set at 60 evaluable patients, in order to be able to conclude with a good level of confidence (>95%) that the abrupt vessel closure rate was less than 10%, if less than 3 abrupt vessel closures were observed. Seventy-one patients were included in the study, of whom 10 needed elective stenting, and were not considered as evaluable for efficacy. Two out of the 61 remaining evaluable patients experienced acute vessel closure during the study period [3.28%, 95% confidence interval (0.4%; 11.4%)]. No major bleeding occurred. The drug plasma concentrations reached 1.91 ± 0.39 mg/l, 10 min after pentasaccharide injection, and decreased on average to 1.18 ± 0.27 mg/l at 2 h, and to 0.36 ± 0.11 mg/l at 23 h after administration of pentasaccharide. Activated clotting time (ACT) and activated partial thromboplastin (aPTT) time remained within normal range. Thrombinantithrombin complex levels fell from 22 ± 17.1 to 4.5 ± 3.4 μg/ml, prothrombin fragment 1+2 levels decreased from 2.15 ± 1.01 to 1.73 ± 0.87, and activated factor VII levels decreased from 43.4 ± 16.8 mU/ml to 18.9 ± 7.3 mU/ml respectively from baseline to 2 h following injection of the tested drug.Conclusions. Administration of pentasaccharide led to the inhibition of thrombin generation without modification of aPTT and ACT. The rate of abrupt vessel closure was within range of rates reported in historical series. Thus we conclude that the anti-thrombotic activity of pentasaccharide, as shown in this pilot trial in the setting of coronary angioplasty, deserves further investigation.